Factors Associated with Antenatal Care Visits at District Of Sungayang Health Center, Tanah Datar Regency In 2017 - Elsa Gebri Utami; Abdiana Abdiana; Ayu Nurdiyan (Universitas Andalas, 2017)
Antenatal care visits is a behavioral form in the utilization of health services to monitor pregnancy in purpose of improving maternal and fetal health. At public health center of Sungayang, the visit for K1 and K4 did not reach the target for the past three years. In 2016 the coverage for K1 was 70,6% dan K4 47,8% meanwhile the public health center target coverage for K1 is 97% and K4 95%. This demonstrate the lack of expectant mothers who make antenatal care visits in accordance with the standardsThis study was a quantitative study with cross sectional design conducted at district of Sungayang health center from November 2016 – September 2017. Population and sample of this research is all of the third trimester pregnant women which amounted to 41 women. Data collected by observation and questionnaire. Data analysis was performed using univariate and bivariate. The results showed 68.3% of pregnant women do antenatal care visits according to the standard. The result of bivariate analysis shows that there is no correlation between age (p = 1,000) and job (p = 0,077), there is correlation between education (p = 0,017), attitude (p = 0,014), and support of husband (p = 0,034) with antenatal care visits at district of Sungayang health center in 2017.There is an association between education, attitude, and support of the husband with antenatal care visits and there is a tendency correlation between knowledge with antenatal care visits.